Contribution of Revista Peruana de Ginecología y Obstetricia to progress of sexual and reproductive rights in Peru - Távara Orozco, Luis (2016)
Objective: To determine the number of articles and topics related to sexual and reproductive rights that have been published in Revista Peruana de Ginecología y Obstetricia since the year 1993 to the year 2015. Methods: We reviewed the electronic records and identified issues related to sexual and reproductive rights published between the years 1993 and 2015, in force period of the current editorial board. Related titles were grouped to facilitate classification and appear correlatively according to their date of publication. Results: A total of 121 articles on sexual and reproductive rights were published in Revista Peruana de Ginecología y Obstetricia, representing 14.58% of the total number of articles in this period. The highest proportion of papers was related to maternal mortality and family planning.